Investment Decision on the Serang–Panimbang Toll Road Project, Taking into Account the Phased Operation of the Toll Road - Wahyu Utomo; Christiono Utomo (Publikasi Indonesia, 2026)
The Serang–Panimbang Toll Road is a National Strategic Project (PSN) developed to support the Tanjung Lesung Special Economic Zone (SEZ) and consists of three sections. Changes in design scope, prolonged approval processes, and delays in land acquisition necessitated a reassessment of the investment under a phased toll road operation scheme. The investment reassessment determines the critical investment decision threshold when the toll road operates in stages. The base case calculation was conducted using Discounted Cash Flow (DCF) with Weighted Average Cost of Capital (WACC) of 13.55% and a 50-year concession period (2019–2069). Net Present Value (NPV) was used as the primary investment decision parameter. Deterministic sensitivity analysis was applied to identify critical turning points, while stochastic sensitivity analysis was conducted using the Monte Carlo method with Crystal Ball through 10,000 trials. The base case yields NPV of IDR 399,084 million, IRR of 13.96%, Discounted Payback Period of 45 years, and Profitability Index of 1.05. Deterministic analysis identifies the most influential variables as toll tariff and construction Capex, with Section 1 operable no later than 2023, Section 2 by 2024, and Section 3 by 2038. The stochastic Monte Carlo simulation reveals an extreme financial risk profile, with a mean NPV of IDR -1,203,368 million and only 468 of 10,000 trials (4.68%) producing NPV > 0. The investment decision probability boundary ranges from 4.20% to 4.68%.